Partial Heart Herniation: An Unusual Manifestation of Trans-Mediastinal Gunshot Injury - Hagar Levy Shachar; Ron Daskal; Yury Peysakhovich; Mansoor Khan; Boris Kessel (Albanian Journal of Trauma and Emergency Surgery, 2025)
Introduction: Gunshot injuries to the thoracic cavity are relatively common and considered high risk for cardiac involvement. However, current literature shows that the incidence of cardiac damage does not differ significantly when comparing various aetiologies of penetrating chest injuries [1].